PENULISAN NAMA TUNGGAL DALAM SERTIPIKAT HAK MILIK DI KOTA YOGYAKARTA DITINJAU DARI PERSPEKTIF ASAS MUTAKHIR - Puspita, Anindya Widha; Hartini (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This research concludes that certificate writing is dominated by men (single) due to religious/belief, socio-cultural and economic factors. Writing a single subject on the certificate doesn’t match the current principles because there is no match physical data and juridical data. Writing names singularly or plurally on a certificate has advantages and disadvantages in terms of the subject, rights and obligations and transferred. Singular and plural subjects physically have the right to use objects, but legally the subject written on the certificate has the right to transfer land rights. The rights and obligations of singular and plural writing are burdened by PBB and BPHTB. In single writing, during the process of transferring inheritance rights, the married couple is burdened by BPHTB unanimously without considering their roles. BPHTB calculation in plural writing reduces the payment obligations of the husband/wife because their role is recognized. When transferring rights to merge objects, objects that are recorded plurally, the merger process is simple because it does not require a name change, whereas in single writing adjustments are made and payments of taxes and other fees.